Detection of the pathogenic parasite Toxoplasma gondii by specific amplification of ribosomal sequences using comultiplex polymerase chain reaction. - Guay, J M (1993)
Amplification of DNA sequences from ribosomal DNA (rDNA) was tested as a specific and sensitive method for the detection of small numbers of Toxoplasma gondii tachyzoite cells. We applied the polymerase chain reaction (PCR) on the basis of detection of the 110-fold repetitive rDNA as a target by using (i) DNA sequences within the small ribosomal subunit known to be universal and conserved in all eukaryotes and (ii) small ribosomal subunit and intergenic spacer rDNA sequences known to be T. gondii species specific. The level of sensitivity obtained from a crude cell lysate allowed the detection of as few as one parasite visualized directly as a specific PCR product in agarose gels. By using a combination of universal and T. gondii species-specific primers, we propose a comultiplex-based PCR approach as a new diagnostic tool. The combination of sensitivity, specificity, and built-in positive and negative PCR controls should make detection of the rDNA sequences by comultiplex PCR a useful clinical test for the diagnosis of toxoplasmosis and for epidemiological studies. Finally, the idea of a built-in positive control to support or counter the T. gondii-specific PCR result is novel and is a notable advance.